Structure of the mouse acidic amino acid decarboxylase GADL1. Issue 1 (26th January 2018) - Raasakka, Arne; Mahootchi, Elaheh; Winge, Ingeborg; Luan, Weisha; Kursula, Petri; Haavik, Jan
Abstract : The structure of the mouse glutamic acid decarboxylase‐like protein 1 (GADL1) is described. The structure provides new insights into the function of GADL1 and related decarboxylases. Abstract : Pyridoxal 5′‐phosphate (PLP) is a ubiquitous cofactor in various enzyme classes, including PLP‐dependent decarboxylases. A recently discovered member of this class is glutamic acid decarboxylase‐like protein 1 (GADL1), which lacks the activity to decarboxylate glutamate to γ‐aminobutyrate, despite its homology to glutamic acid decarboxylase. Among the acidic amino acid decarboxylases, GADL1 is most similar to cysteine sulfinic acid decarboxylase (CSAD), but the physiological function of GADL1 is unclear, although its expression pattern and activity suggest a role in neurotransmitter and neuroprotectant metabolism. The crystal structure of mouse GADL1 is described, together with a solution model based on small‐angle X‐ray scattering data. While the overall fold and the conformation of the bound PLP are similar to those in other PLP‐dependent decarboxylases, GADL1 adopts a more loose conformation in solution, which might have functional relevance in ligand binding and catalysis. The structural data raise new questions about the compactness, flexibility and conformational dynamics of PLP‐dependent decarboxylases, including GADL1.